2022
DOI: 10.1097/mcp.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced comorbidities in patients with sarcoidosis

Abstract: Purpose of reviewSarcoidosis is a chronic multisystemic inflammatory disease of unknown aetiology with a wide range of highly variable clinical manifestations and unpredictable disease course. Sarcoidosis patients may present with specific organ-related symptoms involving functional impairments, and less specific symptoms. The decision whether and when to treat a sarcoidosis patient with pharmacotherapy depends on two major factors: risk of organ failure and/or death and impairment of quality of life. This dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…Renal sarcoidosis after kidney transplantation is rare, usually follows a mild clinical course and is responsive to increased immunosuppression. It has been recently reported that it is safe to perform renal transplantation in sarcoidosis with close clinical and histological monitoring [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal sarcoidosis after kidney transplantation is rare, usually follows a mild clinical course and is responsive to increased immunosuppression. It has been recently reported that it is safe to perform renal transplantation in sarcoidosis with close clinical and histological monitoring [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…physical well-being (Table 4), covers an organ-based approach outlined in prior publications [3,9 ▪▪ ], which accounts for general and sarcoidosis-related health concerns, for example preventive health, concomitant and intercurrent health conditions, as well as sarcoidosis-related disease, complications and symptom management and drug-induced morbidities [3,6 ▪▪ ,9 ▪▪ ,40 ▪▪ ,41 ▪▪ ].…”
Section: Framework For Holistic Well-beingmentioning
confidence: 99%
“…Excluding osteoporosis, there are few studies regarding other musculoskeletal adverse reactions to steroids in sarcoidosis (Drent et al, 2022;Tana et al, 2022). A more common complication is represented by myopathy and avascular necrosis of bone (in particular, osteonecrosis of the femoral head).…”
Section: Muscoloskeletal Systemmentioning
confidence: 99%
“…The impact on the cardiovascular system (CVS) of immunomodulated diseases treated with prolonged steroid therapy is well-known (Pujades-Rodriguez et al, 2020;Galiuto and Volpe, 2021;Giraud et al, 2021;Melani et al, 2021;Drent et al, 2022;Tana et al, 2022).…”
Section: Cardiovascular Systemmentioning
confidence: 99%